Hydrodynamic Equations and Ionization Waves in Fissioning Plasmas - Zhuvanysheva, A.; Kunakov, S. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
the study defines coupled self-consistent Boltzmann equations for fission fragments and created primary electrons are defined for weakly ionized dense plasma irradiated by fission fragments. There has been studied the kinetics of the energy formation of fast particles in a plasma based on the equations. The authors have found and analysed steady-state analytical solutions for fission fragments and the primary electrons’ functions of energy distribution for the helium-3 plasma irradiated by neutron flux. The results of the study have been compared with Monte Carlo energy spectra calculations.